Solid state synthesis, structural characterization and ionic conductivity of bimetallic alkali-metal yttrium borohydrides MY(BH4)4 (M = Li and Na). Issue 22 (19th May 2016) - Roedern, Elsa; Lee, Young-Su; Ley, Morten B.; Park, Kiho; Cho, Young Whan; Skibsted, Jørgen; Jensen, Torben R.
Abstract : Two bimetallic borohydrides, lithium yttrium tetraborohydride, LiY(BH4 )4, and sodium yttrium tetraborohydride, NaY(BH4 )4, have been synthesized by thermal treatment and quenching of ball-milled precursors. Abstract : Two bimetallic borohydrides, lithium yttrium tetraborohydride, LiY(BH4 )4, and sodium yttrium tetraborohydride, NaY(BH4 )4, have been synthesized by thermal treatment and quenching of ball-milled precursors. LiY(BH4 )4 crystallizes in the space group P 4̄2 c and NaY(BH4 )4 in C 2221 and the compounds are isostructural to LiSc(BH4 )4 and NaSc(BH4 )4, respectively. Both LiY(BH4 )4 and NaY(BH4 )4 are built from the complex anions of [Y(BH4 )4 ] − . The unit cell volumes per formula unit of the bimetallic compounds LiY(BH4 )4 and NaY(BH4 )4 are significantly larger compared to those of the constituent components (14% and 7.5% unit cell expansion, respectively), which may contribute to the mobility of the Li + and Na + cations. The ionic conductivities of LiY(BH4 )4 and NaY(BH4 )4 at room temperature, measured by impedance spectroscopy, are σ = 1.26 × 10 −6 and 6.92 × 10 −7 S cm −1 respectively, and are improved compared to those of the precursors. DFT calculations were used to optimize the structures and identify a possible mechanism for the Na ion mobility. In addition, they provide the basis for assignment of the 11 B NMR parameters determined by 11 B MAS NMR for the two boron sites in NaY(BH4 )4 .